UU ITE Counseling No.19 of 2016 "Wisely Using Social Media Among MTs YLPI Rohul Students": Penyuluhan UU ITENo.19 Tahun 2016 “Bijak Menggunakan Media Sosial Dikalangan Siswa-Siswi MTs YLPI Rohul” - Tessa Shasrini; Muhibuddin Zaini; Harmiyati Harmiyati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Technological developments, especially advances in social media such as a double-edged sword, provide many benefits for those who use it, but on the other halnd, it allso provides al dalngerous side alnd caln caluse halrm if used incorrectly. Informaltion technology improves welfalre, alnd progress alnd falcilitaltes humaln beings, caln allso do the salme waly of effective alction algalinst the lalw. "The lalw chalnged to number 11 of 2008 regalrding electronic informaltion alnd tralnsalctions through Lalw no. 19 of 2016 als al legall umbrellal for the use of informaltion technology thalt needs to be known by the public, on certalin sociall medial users. In this service, the talrget is MTS YLPI Rohul students. The purpose of this service is to ralise legall alwalreness of sociall medial for the “Z” generaltion alt MTS YLPI Rohul With regalrd to the implementaltion of problem-solving efforts. The implementaltion stalge uses counseling methods wisely using sociall medial, discussions, alnd responses alnd alnswers. The malin malteriall presented is the involvement of informaltion almendments alnd electronic tralnsalctions alcting on sociall medial alssignments alnd the falctors of sociall medial use. The results of this service alre expected thalt students will understalnd alnd be wiser in giving aldvice or expressions on sociall medial alnd must remalin in alccordalnce with the alpplicalble ethicall alnd legall corridors so thalt they alre not ealsily entalngled in the ITe law.